2020
DOI: 10.1007/s42985-020-00051-x
|View full text |Cite|
|
Sign up to set email alerts
|

Runge–Kutta approximation for $$C_0$$-semigroups in the graph norm with applications to time domain boundary integral equations

Abstract: We consider the approximation of an abstract evolution problem with inhomogeneous side constraint using A-stable Runge–Kutta methods. We derive a priori estimates in norms other than the underlying Banach space. Most notably, we derive estimates in the graph norm of the generator. These results are used to study convolution quadrature based discretizations of a wave scattering and a heat conduction problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…When considering discretizations of the wave equation using boundary integral methods, this is not always the case. Instead, it has been observed that sometimes a "superconvergence phenomenon" appears, where the observed convergence rate surpasses those predicted, see [RSM19a,RSM19b,Rie17].…”
Section: Introductionmentioning
confidence: 98%
“…When considering discretizations of the wave equation using boundary integral methods, this is not always the case. Instead, it has been observed that sometimes a "superconvergence phenomenon" appears, where the observed convergence rate surpasses those predicted, see [RSM19a,RSM19b,Rie17].…”
Section: Introductionmentioning
confidence: 98%
“…When considering discretizations of the wave equation using boundary integral methods, this is not always the case. Instead, it has been observed that sometimes a "superconvergence phenomenon" appears, where the observed convergence rate surpasses those predicted, see [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we present and analyze a fully discrete formulation of the multiplesubdomain acoustic scattering problem based on a Galerkin boundary element method and RK-CQ for the time discretization. Our analysis is based on a pure time-domain point of view, combining ideas by [BLS15a] and [HQSVS17] with the theory of Runge-Kutta approximations of abstract semigroups, as laid out in [AMP03] and recently extended in [RSM20]. A main contribution of the present work is that our analysis covers scattering problems by piecewise constant materials with a very general layout of subdomains.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach therefore generalizes the results of [Qiu16, Chapters 3 and 4], which only allows certain nested geometries (see Section 5). Compared to other works, e.g., [QS16,Qiu16] we also consider RK-CQ using the novel time-domain analysis developed in [RSM20], whereas previous analyses concentrated on multistep methods, whose order, however, is limited to 2 if A-stability is required. These higher order RK-methods suffer from some reduction of order phenomenon in that the convergence order falls somewhere between the stage-and classical order of the RK-method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation